Aplicación del proceso de atención de enfermería en patologías abdominales prevalentes que ingresaron al área de emergencia del Hospital del IESS de Machala durante el año 2012. - Toro Guajala, Marlene Yesenia (2015)
The Nursing Process is a Systematic Method PAE caregiving Humanists, Efficient d centered on the achievements expected results, based on a scientific method by a Professional Nursing, which should provide care for abdominal pathologies such as: Abdominal Pain Syndrome, appendicitis, cholelithiasis and gastroenteritis. One of the demonstrations have been handled in abdominal pathology is acute pain, for which they must manage nursing diagnoses and interventions to achieve results in improved health status of the patient. The most prevalent abdominal pathologies that occur in the first half of 2012 at the Emergency Hospital IESS are: abdominal pain syndrome 146 cases, 50 cases with appendicitis, cholelithiasis, 37 cases were also presented 17 gastroenteritis cases.